Short-term electricity load forecasting with machine learning - Aguilar Madrid, Ernesto (2021)
Aguilar Madrid, E., & Antonio, N. (2021). Short-term electricity load forecasting with machine learning. Information (Switzerland), 12(2), 1-21. [50]. https://doi.org/10.3390/info12020050